Gauging the effectiveness of quantitative forward guidance: evidence from three inflation targeters - Magnus Andersson; Boris Hofmann (European Central Bank (ECB), 2009)
This paper conducts a comparative analysis of the performances of the forward guidance strategies adopted by the Reserve Bank of New Zealand, the Norges Bank and the Riksbank, with the aim to gauge whether forward guidance via publication of an own interest rate path enhances a central bank's ability to steer market expectations. Two main results emerge. First, we find evidence that all three central banks have been highly predictable in their monetary policy decisions and that long-term inflation expectations have been well anchored in the three economies, irrespective of whether forward guidance involved publication of an own interest rate path or not. Second, for New Zealand, we find weak evidence that a publication of a path could potentially enhance a central bank's leverage on the medium term structure of interest rates.
Keywords: E40; E43; E52; 330; central bank communication; forward guidance; monetary policy; Term structure of interest rates; transparency; Geldpolitik; Inflationserwartung; Kommunikation; Zinsstruktur; Zentralbank; Neuseeland; Norwegen; Schweden